The effect of nutritional supplementation on quality of life in people living with HIV: a randomised controlled trial. Issue 6 (11th May 2016) - Tesfaye, Markos; Kaestel, Pernille; Olsen, Mette Frahm; Girma, Tsinuel; Yilma, Daniel; Abdissa, Alemseged; Ritz, Christian; Michaelsen, Kim F.; Hanlon, Charlotte; Friis, Henrik
Abstract: Objective: To determine the effects of lipid‐based nutrient supplements (LNS) on the quality of life of people living with HIV (PLHIV) during the first 3 months of antiretroviral treatment (ART) and to investigate the effects of timing of supplementation by comparing with supplementation during the subsequent 3 months. Methods: A randomised controlled trial was conducted in three ART clinics within public health facilities in Jimma, Ethiopia. Participants were PLHIV eligible to start ART with body mass index >17 kg/m 2 and given daily supplements of 200 g of LNS containing whey or soya either during the first 3 months or the subsequent months of ART. The outcome was measured in terms of total quality‐of‐life scores on the adapted version of the WHOQOL‐HIV‐BREF assessed at baseline, three and six months. Results: Of the 282 participants, 186 (66.0%) were women. The mean age (SD) was 32.8 (±9.0) years, and the mean (SD) total quality‐of‐life score was 82.0 (±14.8) at baseline assessment. At 3 months, participants who received LNS showed better quality of life than those who only received ART without LNS ( β = 6.2, 95% CI: 2.9: 9.6). At 6 months, there was no difference in total quality‐of‐life score between the early and delayed supplementation groups ( β = 3.0, 95% CI: −0.4: 6.4). However, the early supplementation group showed higher scores on the social and spirituality domains than the delayed group. Conclusions: LNS given during the first three months of ART improves the quality of life of PLHIV.